Türk iş hukuku’nda çalışma süreleri ve uygulamada karşılaşılan sorunlar - Uğur, Mustafa (My University, 2002)
Son yıllarda iş hukukunun dayandığı sosyal ve ekonomik temellerde, özellikle teknolojik gelişmelere paralel olarak köklü değişikler meydana gelmiştir. Bu değişikliklerin en önemlilerinden birisi de “çalışma süresi” kavramındaki gelişmelerdir. Tek düze bir çalışma hayatı ve katı kurallarla sınırlanmış “çalışma süresi kavramı, işveren açısından, talep dalgalanmaları ve değişen müşteri ihtiyaçlarını karşılamakta yetersiz kalmakta, çalışanlar açısından ise, sosyal hayatı monotunluğa sürüklemektedir. Bu çalışma ile yürürlükte bulunan 1475 sayılı İş Kanunundaki “çalışma süreleri”ne ilişkin hükümler incelenmekte, mevcut maddelerin gerek işçi, gerekse işverenin ihtiyacını karşılamakta yetersiz olduğu sonucuna varılmaktadır. Bunun en büyük nedeninin, günümüzde endüstrileşmiş ülkelerde de gerçekleştirilen “çalışma sürelerindeki esneklik” uygulamalarının 1475 sayılı İş Kanunundaki mevzuat hükümlerine uygun düşmemesi olduğu anlaşılmaktadır. Name and Surname : Mustafa Uğur Field : Labor Economics and Industrial Relations Programme : Industrial Relations Supervisor : Professor Müjdat Şakar Degree Awarded and Date : Master – November 2002 Working Hours, Flexibility

WORKING HOURS OF THE TURKISH LABOR LAW AND THE FAILURES THAT HAVE BEEN EXPERIENCED DURING THE APPLICATION In recent years, fundemantal variations have occured on the social and economic foundations which are the Turkish Law have based on, parallel with the teknological progressions and changes of individuals’ needs particularly. Developments over “working hours” seem to be one of these crucial variations. A monotonous working life and limited “working hour” by the strict rules, regarding the employer, have tended inadequately for providing of the floating demands and varied customer needs, additionally, have directed the social life through the monotony regarding the workers. The statutes related with “working hours” in the effective Labor Law numbered 1475 have been analyzed by this study and have been concluded that the existing statutes have appeared insufficiently for providing of both workers and employers’ needs. As the most deterministic factor of this issue has been comprehended that the “flexibility of working hours” applications, have been practiced in the industrialized countries would not be matched the legislation statutes of the Labor Law numbered 1475.
Keywords: Hukuk; İş Hukuku; Özel hukuk; Ticaret hukuku